脈動オーロラの輝度値とコーラス波動強度の時間変化に関する統計的比較 - 川村, 勇貴; 細川, 敬祐; 小川, 泰信; 栗田, 怜; John, Wygant; Aaron, Breneman; John, Bonnell; Craig, Kletzing; Yuki, Kawamura; Keisuke, Hosokawa; Yasunobu, Ogawa; Satoshi, Kurita (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object